47. EPIDEMIOLOGICAL AND CLINICAL CHARACTERISTICS OF MALE PATIENTS WITH GENITAL WARTS AT HO CHI MINH CITY HOSPITAL OF DERMATO-VENEREOLOGY (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the epidemiological and clinical characteristics of male patients with genital warts at Ho Chi Minh City Hospital of Dermato-Venereology.Subject and method: A case series of male patients with genital warts for the first time from March 2024 to August 2024.Results: The study subjects had mean age of 23.6 ± 3.6, the age group from 18 - 23 accounted for the majority (53.3%). The percentage of patients with more than one sexual partner accounted for 25%. The MSM group accounted for 70%. The majority of patients had lesions in one location (95%), penis and perianal were the locations with the highest proportion (48.3% and 31.7%). There was a significant difference between the MSM group and the distribution of lesions in the pubic and perianal area (p < 0.05). There was no difference between the number of sexual partners and the locations of lesions (p > 0.05).Conclusion: Investigating epidemiological and clinical characteristics contributes to finding active disease prevention and appropriate treatment methods.
Keywords: Epidemiology; clinical; genital warts in male patients